TAVI-in-TAVI in a patient after alcohol septal ablation - Polaková, Eva; Adlová, Radka; Hájek, Petr; Veselka, Josef (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Cardiovascular medicine at its beginning was dominated by surgical treatment options. The trend of the last decades is heading towards catheterization procedures. Alcohol septal ablation (ASA) was published by Sigwart in 1995 [1] whereas transcatheter aortic valve implantation (TAVI) was performed in 2002 for the first time [2]. Both methods have become efficient therapeutic options not only for patients not suitable for surgery but also for low-risk patients [3–5]. Although the procedures are widely performed, certain challenges remain [6, 7]. Moreover, as patients get older, new difficulties emerge.